Debt Release in the Context of Philosophical and Economic Aspects of Legal Regulation - D. A. Zhestovskaya (Теоретическая и прикладная юриспруденция)
The reform of the rules on debt release (Article 415 of the Civil Code of the Russian Federation) in 2015 raised the question of whether this novelty changed the fundamental principles of civil law. Amendments to the article do not require the consent of the debtor to forgive the debt. Is this a step to the rule that it is not required the consent of the donee in the donation? The author analyzes these amendments on the base of philosophical studies of S. Alekseev and assesses its role in the development of civil law.